Effectiveness of Putra future classroom as a physical learning environment - Muna, Almawaldi (2021)
Traditional physical environment in the university learning space is becoming inadequate due to the changing of learning styles from direct to student centered learning. These traditional models of teaching and learning are being outplaced by the digital revolution of the twenty-first century. The new learning models are no longer supported by the traditional classroom and the university campus design. In order to improve the students’ learning experience, it is imperative to provide physical learning environment that cater the new learning styles and needs. The thesis intends to improve the students’ learning experience by providing a physical learning environment that cater to new learning styles and needs. Thus, the design of future learning spaces in UPM is proposed. The research also aims to provide recommendations and guidelines on creating an innovative physical learning environment of the future through understanding the learning needs of the students in UPM learning facilities and evaluating the elements of a future learning space that can be seen in UPM future classrooms. To achieve that aim, mixed methods of qualitative and quantitative research are used to collect and analyse the data. A visual observation and a student survey are conducted in the future learning spaces. An interview is also conducted to get feedbacks from the lecturers, designers and management staff of the future learning space. A total number of 120 student were surveyed and 17 staffs were interviewed in this research. The data from the survey was analysed using the SPSS (Statistical Product and Service Solutions) software. Descriptive analysis is used to analyse the data from the visual observation, and thematic analysis for interview data analysis. The study finds that while high quality technologies and physical design is used in these spaces, several issues can still be addressed to improve the overall learning environment in terms of physical space layout and function, digital infrastructure and space management. The findings from this study which include the strengths, weaknesses, and issues in the design of future learning spaces in UPM are used in giving recommendations and guidelines to improve these spaces for UPM in their efforts to produce excellent graduate. For further research, the research will encompass bigger samples and other Malaysian universities. The result of the research will contribute towards the improvement of the quality of higher education in Malaysia. In conclusion, UPM is putting efforts on improving the learning environment on the campus. However, by addressing the issues in the findings of this research, the learning environment can be improved even further.